Fish Galectin8-Like Exerts Positive Regulation on Immune Response Against Bacterial Infection - Niu, Jinzhong; Huang, Yu; Liu, Xinchao; Wu, Fenglei; Tang, Jufen; Wang, Bei; Lu, Yishan; Cai, Jia; Jian, Jichang (Frontiers in Immunology, 2020)
Galectin-8 is a member of the galectin family that involved in immune response against pathogen infection. However, the exact roles of fish galectin-8 during pathogen infection require comprehensive studies. In this study, a galectin-8 homologue (OnGal8-like, OnGal8-L) was characterized from Nile tilapia (Oreochromis niloticus) and its roles in response to bacterial infection were analyzed. OnGal8-L contained an open reading frame of 891 bp, encoded a peptide of 296 amino with two CRD regions of tandem-repeat galectin and two carbohydrate recognition sites. The OnGal8-L shared 46.42 % identities to reported Oreochromis niloticus Galectin-8. Transcriptional expression analysis revealed that OnGal8-L was constitutively expressed in all examined tissues and was highly expressed in spleen. The OnGal8-L expression was up-regulated in the spleen, head kidney, and brain following Streptococcus agalactiae (S.agalactiae) challenged. The recombinant OnGal8-L (rOnGal8L) protein could agglutinate erythrocyte, S.agalactiae and A.hydrophila, bind S.agalactiae, A.hydrophila and various PAMPs (lipopolysaccharides, lipoteichoic acid, poly I:C, peptidoglycan, galactose, mannose and maltose) in vitro. Also, rOnGal8L could regulate pro-inflammatory-activity, phagocytosis and respiratory burst of monocytes/macrophages. Moreover, the in vivo analysis showed that OnGal8-L overexpression could protect O.niloticus from S.agalactiae infection through modulating serum antibacterial activity (AKP, ACP, and LZM) and antioxidant capacity (CAT, POD, and SOD), monocytes/macrophages proliferation and cytokine expressions, reducing bacterial burden and decreasing tissue damage. These results collectively indicated that OnGal8-L play important regulatory roles in immune response against bacterial infection.